Violence against women in armed conflicts: pre, during and post - Konstantina Sklavou (Dialogues in Clinical Neuroscience & Mental Health, 2019)
The article will briefly present the problem of violence against women in armed conflict. Violence during war varies in extent and takes distinct forms, sometimes is widespread and yet in other conflicts is quite limited. In conflicts violence takes different forms, sexual slavery, torture in detention, rape, humiliation, discriminations etc. However sexual and gender-based violence in armed conflicts lacks visibility and is not fully understood as it is often labeled as a woman›s only issue and normalizing rape and sexual assault contains the risk of permitting sexual violence and legitimizing its use as a weapon of war.